Flexible, sensitive and rapid humidity-responsive sensor based on rubber/aldehyde-modified sodium carboxymethyl starch for human respiratory detection. (15th April 2023) - Zheng, Zhongjie; Yang, Li; Yang, Yunpeng; Li, Luji; Lin, Baofeng; Fu, Lihua; Xu, Chuanhui
Abstract: Natural polymers with abundant hydrophilic groups are potential candidates for humidity sensor designing. Unfortunately, most of natural polymers lack essential stretchability and high conductivity, which hinder their development in the field of flexible humidity sensor. Cooperation with rubbers and conductive nanometer materials is an effective method to make the best use of natural polymers in flexible humidity sensor. In this paper, a flexible and sensitive sensor with rapid response to humidity change is fabricated based on aldehyde-modified sodium carboxymethyl starch (ACMS), carboxylated styrene-butadiene rubber (XSBR) and Ag nanoflakes through film-forming method. The pre-prepared ACMS owns a better dispersibility in the aqueous phase and serves as reducing agent for formation of Ag nanoflakes. After the film-forming process, the composite film shows a strength of 5.66 MPa and a high stretchability with strain of 367 %. Besides, our sensor shows a rapider response to humidity change than the commercial electronic hygrometer that it takes only 1 s to respond to the humidity change from 25 % RH to 27 % RH. Therefore, the XSBR/ACMS/Ag sensor possesses an impressive sensitive response to slight sweat on human skin and breath, which could find applications in monitoring people's health and distinguish their physical condition.